Young Employees – Work Satisfaction And Motivation - Georgiana-Ionela Bădulescu (Cactus, 2020)
Job satisfaction refers to a set of positive reactions of an employee towards his job. This implies not only economic yield but also social and personal performance, which means that the employee benefits from participating in work activities and also from obtaining personal advantages such as remuneration, a stable job and promotion prospects. Motivation refers to all the incentives and impulses that can push somebody to do something or to aspire to certain goals. This study is based on a research whose aims are to identify what satisfies and what motivates young people at the workplace. The sample consists of 151 young employees with ages ranging from 15 to 29 years old. The concept of job satisfaction is seen in literature and by both employers and employees as a state of wellbeing or a positive mood which results from combining the right amount of employee opinion, work climate and proper motivating management. The resulting work and level of satisfaction is directly influenced by the relationship with the management and co-workers and also by the work conditions. In terms of the stimulating part of motivation, it is shown that employees are feeling satisfied when their merits are considered, when they are rewarded accordingly and when they feel motivated for their next activities.